1948
DOI: 10.1136/bmj.2.4573.441-b
|View full text |Cite
|
Sign up to set email alerts
|

Whooping-cough and Measles

Abstract: CORRESPONDENCE 441 industry, energy and dexterity, and perhaps ambition, the student must be entitled to decide for himself in what direction his work might be expected to bring its own reward. In coming to a decision personal trends must be given due weight:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As shown in figures 3i,j, in this era, we found evidence for an increase in susceptibility to whooping cough following measles infection (u ¼ 36; CI : [16,45]), but this effect is very short-lived (n ¼ 0; CI : [0,1]). The proportion of infectious individuals previously infected with measles (I M /I) was low during the third era, accounting for only 6% of total infectious cases (I) during the peak season (electronic supplementary material, figure S7c).…”
Section: (D) Era III 1946-1956mentioning
confidence: 56%
See 1 more Smart Citation
“…As shown in figures 3i,j, in this era, we found evidence for an increase in susceptibility to whooping cough following measles infection (u ¼ 36; CI : [16,45]), but this effect is very short-lived (n ¼ 0; CI : [0,1]). The proportion of infectious individuals previously infected with measles (I M /I) was low during the third era, accounting for only 6% of total infectious cases (I) during the peak season (electronic supplementary material, figure S7c).…”
Section: (D) Era III 1946-1956mentioning
confidence: 56%
“…Consistent with this, Coleman [15] reported an association between historical measles and whooping cough incidence in the USA, with peak whooping cough incidence lagging measles by approximately three to four weeks. Clinical reports of sequential infections have concluded that the order of exposure was important: whooping cough developing during a measles infection was likely to be more severe [16], while measles infection following whooping cough either had no effect on the severity of either disease [16] or served to ameliorate whooping cough symptoms [17]. As a result of previous empirical experiences, as far back as 1895, it was predicted that if the prevalence of measles could be reduced, it would diminish the death toll from both measles and whooping cough [18].…”
Section: Introductionmentioning
confidence: 99%